2020
DOI: 10.3390/s20143891
|View full text |Cite
|
Sign up to set email alerts
|

Principal Component Thermography for Defect Detection in Concrete

Abstract: The goal of the condition assessment of concrete structures is to gain an insight into current condition of concrete and the existence of defects, which decrease durability and usability of the structure. Defects are quite difficult to detect using infrared thermography when concrete elements cannot be thermally excited with the Sun, together with unfavorable thermophysical properties of concrete structures. In this paper, principal component thermography (PCT) is applied as a post-processing method to a seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…It reaches 700 W/m 2 on a south elevation and 1300 W/m 2 on a horizontal surface at noon [88,148,159]. Previous studies have demonstrated that the larger the energy input is, the higher thermal contrast and SNR are generated in laboratory tests [10,85,139,157,169,170]. In contrast, delamination is difficult to be detected under low or no solar irradiation conditions [20,148,162].…”
Section: Irradiationmentioning
confidence: 99%
See 1 more Smart Citation
“…It reaches 700 W/m 2 on a south elevation and 1300 W/m 2 on a horizontal surface at noon [88,148,159]. Previous studies have demonstrated that the larger the energy input is, the higher thermal contrast and SNR are generated in laboratory tests [10,85,139,157,169,170]. In contrast, delamination is difficult to be detected under low or no solar irradiation conditions [20,148,162].…”
Section: Irradiationmentioning
confidence: 99%
“…Positive SNR means detectable delamination, and negative SNR means undetectable. The advantage of the SNR is that because of signal level evaluation, the metric and criterion can be applied not only to raw IR images but also processed images, such as PPT or PCT [10,169].…”
Section: Metric and Criterionmentioning
confidence: 99%
“…Flights conducted during the experiment have demonstrated the difficulty of manually flying a UAV while capturing NDI data. The data were subject to standard post-processing procedures, such as Principal Component Thermography (PCT) [151] or Pulsed Phase Thermography (PPT) [152]. However, the data were essentially useless due to the noisy sequence, and could not provide accurate results.…”
Section: Aerial Inspection Of Aircraft Wingsmentioning
confidence: 99%
“…Each M column vectors are then subjected to a standardization process to ensure uniformity on a pixel-by-pixel basis. [33,39], This standardized matrix A is then reduced by singular value decomposition as follows:…”
Section: Principal Component Thermography (Pct)mentioning
confidence: 99%
“…This polynomial is referred to as the TSR polynomial. Suggestions based on analytical studies [39] have been made, to determine the degree n of the TSR polynomial that should ideally be used. The optimal degree n depends on the sample under consideration and measurement acquisition parameters, but it is in the range of n = 7 to n = 9 [43].…”
Section: Thermographic Signal Reconstruction (Tsr)mentioning
confidence: 99%